Caste and Devotion: A Casteless Framework for (Some) Forms of Hindu Devotionalism. Issue 4 (9th December 2022) - Gupta, Akshay
ABSTRACT: The caste system has caused widespread oppression within Hinduism. In this paper, I analyze the Bhagavad Gītā (c. 500 BCE–200 CE) and the Bhāgavata Purāṇa (c. 9th century CE), two highly influential Hindu sacred texts, to understand how they conceptualize the relationship between caste and devotion ( bhakti ). I argue that there is a societal framework that does not maintain the caste system but which is consistent with these texts' soteriological vision and can be implemented in lieu of such a system. This framework demonstrates that for certain forms of Hindu religiosity, caste is not essential to uphold from a scriptural perspective. Given this framework, the caste system can be challenged and interrogated to a significant extent and alternative societal frameworks can be proposed. I also consider and respond to objections to the framework I put forth.